9(x+6)-5(2x-7)=22

Simple and best practice solution for 9(x+6)-5(2x-7)=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+6)-5(2x-7)=22 equation:


Simplifying
9(x + 6) + -5(2x + -7) = 22

Reorder the terms:
9(6 + x) + -5(2x + -7) = 22
(6 * 9 + x * 9) + -5(2x + -7) = 22
(54 + 9x) + -5(2x + -7) = 22

Reorder the terms:
54 + 9x + -5(-7 + 2x) = 22
54 + 9x + (-7 * -5 + 2x * -5) = 22
54 + 9x + (35 + -10x) = 22

Reorder the terms:
54 + 35 + 9x + -10x = 22

Combine like terms: 54 + 35 = 89
89 + 9x + -10x = 22

Combine like terms: 9x + -10x = -1x
89 + -1x = 22

Solving
89 + -1x = 22

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-89' to each side of the equation.
89 + -89 + -1x = 22 + -89

Combine like terms: 89 + -89 = 0
0 + -1x = 22 + -89
-1x = 22 + -89

Combine like terms: 22 + -89 = -67
-1x = -67

Divide each side by '-1'.
x = 67

Simplifying
x = 67

See similar equations:

| -.5(z-2.4)=6 | | -11-18(8f+7)= | | 25=(.5)(6+4)(x) | | -4v=-23 | | -4(-5w+5)3w=5(w-5)-53 | | 8?-5=-40 | | 5(-4w+14)= | | c=d-f | | cx-10=-5forx | | -4(5x+7)=92 | | (x-2)(x+4)+6(x+2)(x-2)=x^2-4 | | 8+(-3)=9 | | [5h+2]=-8 | | 200=20x+100 | | 5(12k-17)= | | 77=17+6x | | 6n-6=6-5n | | 35x+x=3x+14 | | 6u-7=3 | | [2t-4]=8 | | 2(5x-8)-5(3x+5)=-5x | | 7x+8=3x+29 | | -2x+4=x+7 | | -6(6+5a)=-66 | | (-3)-2(x+6)=-5 | | -1=-.5x+2 | | 9w+33=3(w-9) | | 825+3.25x=8.20x | | X-(-2)=-6 | | -7y+5=4 | | 900=5e^9x | | (14x-5)+13x=180 |

Equations solver categories